1997
DOI: 10.1007/s004649900545
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic nasobiliary drainage for bile duct injury after laparoscopic cholecystectomy

Abstract: Bile duct injuries are a potential complication of laparoscopic cholecystectomy (LC). A patient who underwent successful endoscopic nasobiliary drainage (ENBD) for a bile duct injury sustained during LC is presented. Of particular note, the patient also had Chilaiditi's syndrome. A 59-year-old woman was admitted with symptomatic cholecystolithiasis and Chilaiditi's syndrome. LC was performed. Postoperatively, the patient complained of abdominal discomfort. Laboratory examination revealed cholestasis. Bilious m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…Although accessory bile ducts of Luschka (also called supravesicular ducts) do not drain any liver parenchyma, they can be a source of bile leak or biliary peritonitis after cholecystectomy [25]. Less common are the leaks from damage to the CBD or proximal hepatic ducts [10,[12][13][14][15][16][17][18][19]. Therapy for bile leak includes percutaneous drainage of fluid collections (bilomas), therapeutic ERCP, and surgery.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although accessory bile ducts of Luschka (also called supravesicular ducts) do not drain any liver parenchyma, they can be a source of bile leak or biliary peritonitis after cholecystectomy [25]. Less common are the leaks from damage to the CBD or proximal hepatic ducts [10,[12][13][14][15][16][17][18][19]. Therapy for bile leak includes percutaneous drainage of fluid collections (bilomas), therapeutic ERCP, and surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The objective of endoscopic intervention is to abolish the pressure gradient across the sphincter of Oddi, thereby promoting preferential bile flow into the duodenum and allowing the leak to heal [26]. This can be successfully achieved by a diversity of techniques, including biliary sphincterotomy, stent insertion (with or without sphincterotomy), or nasobiliary tube drainage alone [10,[12][13][14][15][16][17][18][19]. Treatment success has ranged from 85% to 100% in most studies, with very low complication rates reported for all endoscopic treatment modalities [10,[12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of BDI during LC is higher than that in open cholecystectomy [8,14,18,36,43], in which rates less than 0.25% have mostly been reported (range, 0.1-0.6%) [4,15,29,40]. Therefore, improvement of safety standards in LC depends strictly on the decrease of biliary tract injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the injuries related to laparoscopic cholecystectomy can be managed by endoscopic techniques [7], laparoscopic management of these injuries is poor. In this clinical study, we investigated the efficacy of laparoscopic management of the bile duct and bowel injuries during laparoscopic cholecystectomy.…”
mentioning
confidence: 99%